Representasi Kesetaraan Gender Pada Iklan Alfamart X GoPay #Kebahagiaankecil Untuk Kita Semua - Nabilah Ardelia, Talitha (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
Advertising media is one of the media that contributes to the process of socializing gender stereotypes in society. Nowadays, awareness of gender equality is increasing, advertising media can play a role in socializing the issue of gender equality as one of the realities that exist in society. Alfamart X GoPay advertisements was taken as the object of research to understand the description and meaning of gender equality through visuals and narratives with descriptive qualitative approaches and semiotic analysis. The result of the semiotic analysis on the advertisement is that men can play a dual role both in supporting the family economy and in the domestic sphere. Household work should be done by anyone, both men and women.